Plasmablastic multiple myeloma is associated with increased vascular endothelial growth factor immunoexpression - Ribas, C. [UNIFESP] (2005)
The biologic basis of the negative prognosis of plasmablastic myeloma is not fully understood. To determine whether histologically aggressive multiple myeloma (MM) is associated with a more angiogenic marrow environment, bone marrow samples from 50 recently diagnosed MM patients were evaluated. Twelve percent (6/50) of patients presented plasmablastic MM, and this feature correlated with moderate/strong intensity of vascular endothelial growth factor staining of plasma cells (P = 0.036). Although plasmablastic MM was not associated with increasing of microvessel density, this new evidence of increased expression of vascular endothelial growth factor on plasmablasts suggests that the adverse prognosis conferred by plasmablastic disease may be due, at least in part, to secretion of this angiogenic cytokine, also suggesting that the subset of MM patients with plasmablastic features may derive particular benefit from antiangiogenic therapies.